Effects of renal denervation therapy on cardiac function and malignant arrhythmia in patients with reduced left ventricular ejection fraction and narrow QRS complexes treated with implantable cardioverter defibrillator - Yang, Wei; Xu, You-Long; Gao, Jun-Qing; Shen, Deng; Li, Min; Fa, Jing-Jing; Zhang, Ying; Wang, Rui; Hou, Shu-Xin; Hu, Wen-Ying; Jin, Hui-Gen; Liu, Zong-Jun (Frontiers in Physiology, 2022)
Objective: The purpose of this study was to explore the effects of renal denervation (RDN) on cardiac function and malignant arrhythmia in patients with reduced left ventricular ejection fraction (HFrEF) and narrow QRS treated with an implantable cardioverter defibrillator (ICD). Methods: A total of 20 eligible HFrEF patients [left ventricular ejection fraction (LVEF) <40%] and narrow QRS complexes (QRS duration <120 ms) were randomized into either the ICD plus RDN group or the ICD only group during 17 April 2014 to 22 November 2016. Clinical data, including clinical characteristics, blood biochemistry, B-type natriuretic peptide, echocardiographic indexes, 6-min walk distance (6MWD), New York Heart Association (NYHA) classification, and count of ICD discharge events before and after the operation were analyzed. Patients were followed up for up to 3 years post ICD or ICD plus RDN. Results: Baseline clinical data were comparable between the two groups. Higher LVEF (%) (mixed model repeated measure, p = 0.0306) (39.50% ± 9.63% vs. 31.20% ± 4.52% at 1 year; 41.57% ± 9.62% vs. 31.40% ± 8.14% at 3 years), systolic blood pressure (p = 0.0356), and longer 6MWD (p < 0.0001) as well as reduction of NYHA classification (p < 0.0001) were evidenced in the ICD plus RDN group compared to ICD only group during follow-up. Patients in the ICD plus RDN group experienced fewer ICD discharge events (2 vs. 40) and decreased diuretic use; rehospitalization rate (30% vs. 100%, p = 0.0031) and cardiogenic mortality rate (0% vs. 50%, p = 0.0325) were also significantly lower in the ICD plus RDN group than in the ICD only group during follow-up. Conclusion: ICD implantation plus RDN could significantly improve cardiac function and cardiac outcome as well as increase exercise capacity compared to ICD only for HFrEF patients with narrow QRS complexes.